Concurrent Pulmonary and Cerebellar Cryptococcus Gattii Cryptococcoma in an Apparently Immunocompetent Patient in Florida - Benjamin Billings; Neeka Akhavan; Amy Vittor; Ying Nagoshi (Case Reports in Infectious Diseases)
Cryptococcus infection is caused by one of the two species, Cryptococcus neoformans, or the less common Cryptococcus gattii. While Cryptococcus neoformans commonly infects the immunocompromised population, Cryptococcus gattii has been seen more frequently in immunocompetent patients. Many seemingly immunocompetent patients, however, may have unidentified underlying immunodeficiencies. Recently, antigranulocyte-macrophage colony-stimulating (GM-CSF) antibodies have been identified as a risk factor for cryptococcosis. We describe a case of disseminated Cryptococcus gattii infection in a seemingly immunocompetent young man, who is found to have anti-GM-CSF antibodies.